Penggunaan Media Pembelajaran Papan Tulis Interaktif di Kelas Pada Abad 21 - Lebyana Norma Belinda; Sofyan Iskandar; Dede Trie Kurniawan (Universitas Muhammadiyah Kuningan, 2023)
This study aims to find out how to use interactive whiteboard learning media in the classroom in the 21st century. The research method used in this research is qualitative research which is a literature study (library research). Data collection techniques by conducting a review of books, literature, journals, the internet, the results of thesis and dissertation research. Data analysis techniques in this study emphasize references or libraries as a reference. Learning in the 21st century is creative and innovative learning with the use of interactive whiteboard learning media in the classroom so it can bring positive changes in learning in the 21st century. It can be concluded that this interactive whiteboard learning model is suitable as an innovative learning medium. Based on the results of the preliminary study, it shows that this interactive whiteboard learning media is effective and not monotonous and based on a literature study, this interactive whiteboard has many advantages.